Beyond the predicted: expanding our understanding of creative agency in international development through practice and policy. Issue 1 (2nd January 2017) - Stupples, Polly
Abstract : This article analyses the framing of creative agency within the field of international development before going on to challenge some of the limitations of that framing. The critique is informed by research undertaken with artist-led initiatives in Central America that reveals the political implications of that framing and, at the same time, points to alternative forms of creative agency at work. The paper highlights the approaches of a number of international development donors whose policies appear able to support more expansive and emancipatory conceptions of agency for artists and artist-led initiatives, and makes a claim for the political importance of such policy platforms, despite some on-going limitations.